Sistem Pendidikan di Korea Selatan - lulhairo, Mirza; Sassi, Komarudin; Noviani, Dwi (STAI Denpasar Bali, 2023)
South Korea have many things interested and make we have to find it more, not only about the culture but also abaout the education. The development of education in South Korea can be implemented with eitherbecause of the educational reforms undertaken by the government annualy in order to answer the challenges of the growing period. A long history on the history of education in South Korea that interest the researcher to examine how big the impact of the renewal of education towards the progress of national education. On 1999, the government launched the Brain Korea 21st project as on of the government’s ambitious program to improve the competitve power of the nation of Korea. The main question was “How the implementation of Brain Korea 21st project and the impacts for South Korea in 1999 – 2005?”. To answer that problem, the researcher implead a history method and literature technique there are books and journals. Based the research and the conclusion was, first the Brain Korea 21st project which was launched by the goverment on 1999 is a project initiated during 7 years with various objective impact on the socio-cultural aspect was gender equally during this so the issue in South Korea as well the increasing suicides and the emergence of the social gap between professors at the local University. Second the impact of which was felt in the aspect of economy is pulling back the number of foreign investors after implemented the Brain Korea 21st project.